Use of a catalyst in the reaction of CO reducing NO in catalytic mixture
Patent Information
- Application Number
- CN202310472115.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-04-27
AI Technical Summary
[0003]目前商业上使用的三效催化剂主要使用高载量Pt,Pd,Rh等贵金属作为活性成分,而贵金属价格昂贵,这使三效催化剂的成本很高
[0025] 1. The preparation method of supported noble metal catalysts is simple and easy to control. The active metal in the prepared catalyst is highly dispersed and exists in the form of a single-atom alloy;
Smart Images

Figure HDA0004204403470000011
Abstract
Description
Technical Field
[0001] This invention relates to the application of a TiO2 nanosheet-supported Pt,Ni single-atom alloy catalyst in the CO-NO reduction reaction during automobile exhaust purification. Background Technology
[0002] In recent years, with the development of society, economy, and technology, the number of motor vehicles has experienced explosive growth. The harm of vehicle exhaust to the environment and human health has become increasingly serious. NO in exhaust gases, in particular, can cause environmental problems such as acid rain, ozone depletion, and photochemical smog, seriously threatening human health. Therefore, the requirements for vehicle exhaust purification are becoming increasingly stringent, and how to efficiently purify NO in exhaust gases has become an urgent problem to be solved.
[0003] Currently, commercially used three-way catalysts mainly use high loadings of precious metals such as Pt, Pd, and Rh as active components. However, these precious metals are expensive, making three-way catalysts very costly. Therefore, the need to reduce the loading of precious metals is becoming increasingly urgent. Developing low-precious-metal catalysts is an inevitable trend. Single-atom catalysts have attracted widespread attention because they maximize atom utilization and exhibit catalytic activity not found in particulate catalysts. Therefore, the question arises: can we synthesize single-atom alloy catalysts, while ensuring that the precious metals are dispersed at single atoms, and through the synergistic effect of the two metals forming the alloy, change the properties of the active center, thereby significantly improving catalytic activity while effectively reducing the amount of precious metals used? Summary of the Invention
[0004] One object of the present invention is to provide a TiO2 nanosheet-supported Pt,Ni single-atom alloy catalyst.
[0005] The second objective of this invention is to provide a method for preparing a TiO2 nanosheet-supported Pt,Ni single-atom alloy catalyst.
[0006] The third objective of this invention is to provide an application of a TiO2 nanosheet-supported Pt,Ni single-atom alloy catalyst.
[0007] To achieve the above objectives, the present invention provides a TiO2 nanosheet-supported Pt,Ni single-atom alloy catalyst, the preparation method of which includes the following steps:
[0008] 1) Synthesis of anatase TiO2 nanosheets;
[0009] The nanosheets were synthesized from a titanium source and an acid, with a molar ratio of acid to titanium source of 0.5-2. After thorough stirring, the mixture was transferred to a polytetrafluoroethylene (PTFE) liner, which was then placed in a hydrothermal reactor. After high-temperature crystallization, the product was centrifuged, washed with deionized water and ethanol, and then dried to obtain TiO2 nanosheets.
[0010] Preferably, the molar ratio of acid to titanium source is 0.8-1.
[0011] Preferably, the titanium source is tetrabutyl titanate or tetraisopropyl titanate.
[0012] Preferably, the acid is hydrofluoric acid.
[0013] Preferably, the high-temperature crystallization temperature is 180-200℃, and the crystallization time is 20-36h. More preferably, the crystallization temperature is 200℃, and the crystallization time is 24h.
[0014] 2) Synthesis of catalysts for TiO2-supported Pt and Ni single-atom alloys;
[0015] Pt and Ni precursors were dissolved in water and mixed evenly with the prepared TiO2 nanosheets. The mixed slurry was freeze-dried, calcined in a muffle furnace, and then reduced under a hydrogen atmosphere to obtain a catalyst of TiO2-supported Pt and Ni single-atom alloy.
[0016] Preferably, the Pt precursor is chloroplatinic acid, and the Ni precursor is nickel nitrate or nickel acetate.
[0017] Preferably, the concentration of the Pt precursor is 5 mmol·L⁻¹. -1 -50mmol·L -1 More preferably, the concentration of the Pt precursor is 20 mmol·L⁻¹. -1 -30mmol·L -1 .
[0018] Preferably, the concentration of the Ni precursor is 680 mmol·L⁻¹. -1 -1700 mmol·L -1 More preferably, the concentration of the Ni precursor is 850 mmol·L⁻¹. -1 -1200 mmol·L -1 .
[0019] Preferably, the calcination temperature is 400-500℃ and the time is 2-3 hours.
[0020] Preferably, the hydrogen concentration for reduction is 5%-100%. The reduction temperature is 400-500℃, and the reduction time is 1-3 hours.
[0021] The catalytic activity testing method for the supported catalyst provided by this invention is as follows:
[0022] Granulated catalyst was added to a fixed bed and reduced under a hydrogen atmosphere for 2-3 hours. After cooling to room temperature, a mixture of CO and NO (concentration 0.1%-0.5%, with He as the equilibrium gas) was introduced. The reaction program was as follows: 50℃ for 30 min, increased to 100℃ for 30 min, increased to 150℃ for 30 min, increased to 200℃ for 30 min, increased to 250℃ for 30 min, increased to 300℃ for 30 min, increased to 350℃ for 30 min, and increased to 400℃ for 30 min. The concentration of the product in the tail gas was detected by chromatography.
[0023] This catalyst, when applied to the CO-NO reduction reaction, exhibits excellent low-temperature activity and selectivity for the target product N2.
[0024] The present invention has the following effects:
[0025] 1. The preparation method of supported noble metal catalysts is simple and easy to control. The active metal in the prepared catalyst is highly dispersed and exists in the form of a single-atom alloy;
[0026] 2. The prepared catalyst exhibits good catalytic activity and selectivity in the CO-NO reduction reaction, with a N2 selectivity of over 90% in the product, and also demonstrates high stability. Attached image description:
[0027] Figure 1 This is a high-angle annular dark-field image of the single-atom alloy catalyst in the embodiment; Detailed Implementation
[0028] Example 1:
[0029] 1) Mix 10 ml of tetrabutyl titanate and 1.0 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 200 °C for 20 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase phase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm. 2) Dissolve 0.011 g of chloroplatinic acid and 0.248 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce under a 5% hydrogen atmosphere (He gas equilibrium) for 2 h. Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst is obtained. HAADF-STEM characterization shows that Pt is uniformly dispersed in the form of single atoms on the second metal component Ni, and the Ni particle size is between 4-10 nm.
[0030] Example 2:
[0031] 1) Mix 12.5 ml of tetrabutyl titanate and 3 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 200 °C for 20 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm. 2) Dissolve 0.011 g of chloroplatinic acid and 0.248 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization shows that Pt is uniformly dispersed in the second metal component Ni in the form of single atoms, and the Ni particle size is between 4-10 nm.
[0032] Example 3:
[0033] 1) Mix 25 ml of tetrabutyl titanate and 3 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 200 °C for 20 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm.
[0034] 2) Dissolve 0.011 g of chloroplatinic acid and 0.248 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization showed that Pt was uniformly dispersed in the second metal component Ni in the form of single atoms, and the Ni particle size was between 4-10 nm.
[0035] Example 4:
[0036] 1) Mix 10 ml of tetrabutyl titanate and 1.0 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 200 °C for 20 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase phase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2The thickness is approximately 10-20 nm. 2) Dissolve 0.011 g of chloroplatinic acid and 0.496 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization shows that Pt is uniformly dispersed in the form of single atoms on the second metal component Ni, and the Ni particle size is between 4-10 nm.
[0037] Example 5:
[0038] 1) Mix 12.5 ml of tetrabutyl titanate and 3 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 200 °C for 20 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm. 2) Dissolve 0.011 g of chloroplatinic acid and 0.496 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization shows that Pt is uniformly dispersed in the form of single atoms on the second metal component Ni, and the Ni particle size is between 4-10 nm.
[0039] Example 6:
[0040] 1) Mix 25 ml of tetrabutyl titanate and 3 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 200 °C for 20 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm.
[0041] 2) Dissolve 0.011 g of chloroplatinic acid and 0.496 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization showed that Pt was uniformly dispersed in the second metal component Ni in the form of single atoms, and the Ni particle size was between 4-10 nm.
[0042] Example 7:
[0043] 1) Mix 10 ml of tetrabutyl titanate and 1.0 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 180 °C for 36 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm. 2) Dissolve 0.011 g of chloroplatinic acid and 0.248 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization shows that Pt is uniformly dispersed in the second metal component Ni in the form of single atoms, and the Ni particle size is between 4-10 nm.
[0044] Example 8:
[0045] 1) Mix 12.5 ml of tetrabutyl titanate and 3 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 180 °C for 36 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm.
[0046] 2) Dissolve 0.011 g of chloroplatinic acid and 0.248 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization showed that Pt was uniformly dispersed in the second metal component Ni in the form of single atoms, and the Ni particle size was between 4-10 nm.
[0047] Example 9:
[0048] 1) Mix 25 ml of tetrabutyl titanate and 3 ml of hydrofluoric acid (40 wt%, AR) in a hydrothermal reactor and react hydrothermally at 180 °C for 36 h. Wash the solid product successively with deionized water and ethanol, and dry at 60 °C for 8 h to obtain anatase TiO2 nanosheets with a size of approximately 2000-3000 nm. 2 The thickness is approximately 10-20 nm.
[0049] 2) Dissolve 0.011 g of chloroplatinic acid and 0.248 g of nickel nitrate in 1 ml of water, add to 1 g of TiO2 nanosheets, stir, freeze-dry, calcine at 400 °C for 2 h, and then reduce for 2 h under a 5% hydrogen atmosphere (He gas equilibrium). Electron microscopy images show that a TiO2-supported Pt, Ni single-atom alloy catalyst was obtained. HAADF-STEM characterization showed that Pt was uniformly dispersed in the second metal component Ni in the form of single atoms, and the Ni particle size was between 4-10 nm.
[0050] Application Example 1:
[0051] 100 mg of the catalyst prepared in Example 1 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, then increased to 100°C for 30 min, then increased to 150°C for 30 min, then increased to 200°C for 30 min, then increased to 250°C for 30 min, then increased to 300°C for 30 min, then increased to 350°C for 30 min, and finally increased to 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 15% and the CO conversion rate was 11%. At 150°C, the NO conversion rate was 37% and the CO conversion rate was 32%. At 200°C, the NO conversion rate was 75% and the CO conversion rate was 72%. At temperatures above 250℃ up to 400℃, NO is completely converted, and the N2 selectivity among the NO conversion products is 95%, with only a small amount of N2O as a byproduct.
[0052] Application Example 2:
[0053] 100 mg of the catalyst prepared in Example 2 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, 100°C for 30 min, 150°C for 30 min, 200°C for 30 min, 250°C for 30 min, 300°C for 30 min, 350°C for 30 min, and 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 14% and the CO conversion rate was 9%. At 150°C, the NO conversion rate was 38% and the CO conversion rate was 34%. At 200°C, the NO conversion rate was 76% and the CO conversion rate was 73%. At temperatures above 250℃ up to 400℃, NO is completely converted, with a N2 selectivity of 94% in the product and only a small amount of N2O as a byproduct.
[0054] Application Example 3:
[0055] 100 mg of the catalyst prepared in Example 3 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, then increased to 100°C for 30 min, then increased to 150°C for 30 min, then increased to 200°C for 30 min, then increased to 250°C for 30 min, then increased to 300°C for 30 min, then increased to 350°C for 30 min, and finally increased to 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 15% and the CO conversion rate was 10%. At 150°C, the NO conversion rate was 40% and the CO conversion rate was 35%. At 200°C, the NO conversion rate was 77% and the CO conversion rate was 74%. At temperatures above 250℃ up to 400℃, NO is completely converted, with a N2 selectivity of 95% in the products and only a small amount of N2O as a byproduct.
[0056] Application Example 4:
[0057] 100 mg of the catalyst prepared in Example 4 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, then increased to 100°C for 30 min, then increased to 150°C for 30 min, then increased to 200°C for 30 min, then increased to 250°C for 30 min, then increased to 300°C for 30 min, then increased to 350°C for 30 min, and finally increased to 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 7% and the CO conversion rate was 3%. At 150°C, the NO conversion rate was 30% and the CO conversion rate was 24%. At 200°C, the NO conversion rate was 66% and the CO conversion rate was 60%. At temperatures above 250℃ up to 400℃, the NO conversion rate is 90%, and the CO conversion rate is 88%. The N2 selectivity in the products is 85%, with the remainder being the byproduct N2O.
[0058] Application Example 5:
[0059] 100 mg of the catalyst prepared in Example 5 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, 100°C for 30 min, 150°C for 30 min, 200°C for 30 min, 250°C for 30 min, 300°C for 30 min, 350°C for 30 min, and 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 8% and the CO conversion rate was 4%. At 150°C, the NO conversion rate was 31% and the CO conversion rate was 24%. At 200°C, the NO conversion rate was 70% and the CO conversion rate was 65%. At temperatures above 250℃ up to 400℃, the NO conversion rate is 92%, and the CO conversion rate is 90%. The N2 selectivity in the products is 87%, with the remainder being the byproduct N2O.
[0060] Application Example 6:
[0061] 100 mg of the catalyst prepared in Example 6 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, then increased to 100°C for 30 min, then increased to 150°C for 30 min, then increased to 200°C for 30 min, then increased to 250°C for 30 min, then increased to 300°C for 30 min, then increased to 350°C for 30 min, and finally increased to 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 7% and the CO conversion rate was 5%. At 150°C, the NO conversion rate was 35% and the CO conversion rate was 30%. At 200°C, the NO conversion rate was 71% and the CO conversion rate was 66%. At temperatures above 250℃ up to 400℃, the NO conversion rate is 92%, and the CO conversion rate is 91%. The N2 selectivity among the products is 88%, with the remainder being the byproduct N2O.
[0062] Application Example 7:
[0063] 100 mg of the catalyst prepared in Example 7 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, 100°C for 30 min, 150°C for 30 min, 200°C for 30 min, 250°C for 30 min, 300°C for 30 min, 350°C for 30 min, and 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 16% and the CO conversion rate was 10%. At 150°C, the NO conversion rate was 38% and the CO conversion rate was 32%. At 200°C, the NO conversion rate was 76% and the CO conversion rate was 71%. At temperatures above 250℃ up to 400℃, NO is completely converted, with a N2 selectivity of 97% in the product and only a small amount of N2O as a byproduct.
[0064] Application Example 8:
[0065] 100 mg of the catalyst prepared in Example 8 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, 100°C for 30 min, 150°C for 30 min, 200°C for 30 min, 250°C for 30 min, 300°C for 30 min, 350°C for 30 min, and 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 17% and the CO conversion rate was 14%. At 150°C, the NO conversion rate was 41% and the CO conversion rate was 37%. At 200°C, the NO conversion rate was 79% and the CO conversion rate was 74%. At temperatures above 250℃ up to 400℃, NO is completely converted, with a N2 selectivity of 94% in the product and only a small amount of N2O as a byproduct.
[0066] Application Example 9:
[0067] 100 mg of the catalyst prepared in Example 9 was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)) was introduced. The reaction program was as follows: 50°C for 30 min, 100°C for 30 min, 150°C for 30 min, 200°C for 30 min, 250°C for 30 min, 300°C for 30 min, 350°C for 30 min, and 400°C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 100°C, at which point the NO conversion rate was 14% and the CO conversion rate was 11%. At 150°C, the NO conversion rate was 38% and the CO conversion rate was 33%. At 200°C, the NO conversion rate was 77% and the CO conversion rate was 74%. At temperatures above 250℃ up to 400℃, NO is completely converted, with a N2 selectivity of 93% in the product and only a small amount of N2O as a byproduct.
[0068] Comparative Example 1:
[0069] 100 mg of a catalyst containing Pt nanoparticles supported on TiO2 (prepared by an equal-volume impregnation method, with a loading of 0.5%, named Pt NP-TiO2) was used. The Pt particle size was between 0.4 nm and 1.4 nm. This catalyst was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO was introduced (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)). The reaction program was as follows: 50 °C for 30 min, then increased to 100 °C for 30 min, then increased to 150 °C for 30 min, then increased to 200 °C for 30 min, then increased to 250 °C for 30 min, then increased to 300 °C for 30 min, then increased to 350 °C for 30 min, and finally increased to 400 °C for 30 min. The tail gas was subjected to chromatographic analysis. Activity was observed at 150 °C, at which point the NO conversion rate was 5% and the CO conversion rate was 4%. At 200℃ to 300℃, the NO conversion rate is 10% and the CO conversion rate is 8%. At 350℃, the NO conversion rate is 25% and the CO conversion rate is 21%. At 400℃, the NO conversion rate is 59% and the CO conversion rate is 55%. At this point, the N2 selectivity in the product is 39%, and the remaining product is the byproduct N2O.
[0070] Comparative Example 2:
[0071] 100 mg of a Ni nanoparticle-supported catalyst (prepared by equal-volume impregnation method, loading 5%, named Ni NP-TiO2) with Ni particle size between 10-27 nm was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO was introduced (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)). The reaction program was as follows: 50℃ for 30 min, increased to 100℃ for 30 min, increased to 150℃ for 30 min, increased to 200℃ for 30 min, increased to 250℃ for 30 min, increased to 300℃ for 30 min, increased to 350℃ for 30 min, and increased to 400℃ for 30 min. The tail gas was analyzed by chromatography. During the reaction, the NO conversion rate was 0%, the CO conversion rate was 0%, and the N2 selectivity in the product was 0%.
[0072] Comparative Example 3:
[0073] 100 mg of a catalyst, Pt and Ni ordinary alloy nanoparticles supported on TiO2 (prepared by equal volume impregnation method, Pt loading 0.5%, Ni loading 0.5%, named PtNi NP-TiO2), was used. Pt and Ni formed an ordinary alloy with particle size between 4-10 nm. This catalyst was granulated to 40-60 mesh and added to a fixed-bed quartz tube. A reaction gas of 0.2% CO and 0.2% NO was introduced (He gas equilibrium, volume hourly space velocity 20000 ml / (g*h)). The reaction program was as follows: 50℃ for 30 min, increased to 100℃ for 30 min, increased to 150℃ for 30 min, increased to 200℃ for 30 min, increased to 250℃ for 30 min, increased to 300℃ for 30 min, increased to 350℃ for 30 min, and increased to 400℃ for 30 min. When the exhaust gas is passed through a chromatogram, it shows almost no activity between 50°C and 200°C. At 250°C, the NO conversion rate is 25% and the CO conversion rate is 23%. At 300°C, the NO conversion rate is 80% and the CO conversion rate is 74%. Between 350°C and 400°C, the NO conversion rate is 85% and the CO conversion rate is 80%. At this point, the N2 selectivity in the product is 41%, and the remaining product is the byproduct N2O.
[0074] Results Analysis
[0075] Based on the comparison between Application Examples 1-9 and Comparative Example 1, the catalytic activity of the Pt-Ni alloy is significantly better than that of the single Pt catalyst, indicating that Pt and Ni have a significant synergistic promoting effect on this reaction.
[0076] Comparing Application Examples 1-9 with Comparative Example 2, the Ni catalyst itself is inactive, while adding a small amount of Pt to Ni can greatly improve its catalytic activity. This indicates that Pt is an essential active component in this reaction, while Ni is an excellent promoter.
[0077] Comparing Application Examples 1-9 with Comparative Example 3, the performance of the Pt,Ni single-atom alloy catalyst is significantly superior to that of the ordinary Pt,Ni alloy catalyst. This demonstrates the advantage of single atoms in this reaction. By forming a single-atom alloy, Pt and Ni alter the electron density of Pt due to the unique electronic effect between the bimetals, effectively improving the conversion rate of NO and the selectivity of N2.
Claims
1. The application of a catalyst in the CO-NO reduction reaction in a catalytic mixture, characterized in that: The catalyst uses TiO2 as a support and loads Pt and Ni as active components; the loading of Pt relative to the support is 0.1-1 wt%, and the loading of Ni relative to the support is 4-10 wt%. The catalyst preparation process is as follows: 1) Synthesis of anatase TiO2 nanosheets; The synthesis of nanosheets consists of a titanium source and an acid, wherein the molar ratio of the acid to the titanium source is 0.5-2. After the titanium source and the acid are mixed and stirred evenly, they are placed in a hydrothermal reactor for high-temperature crystallization. After the high-temperature crystallization is completed, the product is centrifuged and the solid product is dried to obtain TiO2 nanosheets. The crystallization temperature is 180-200℃ and the crystallization time is 20-36 hours. 2) Synthesis of TiO2-supported Pt and Ni catalysts; Pt and Ni precursors were dissolved in water and mixed evenly with the prepared TiO2 nanosheets. The mixed slurry was freeze-dried and then calcined in a muffle furnace at 400-500℃ for 2-3 hours. Before the reaction, it was reduced at 400℃ for 1-2 hours in an atmosphere containing 5%-100% hydrogen by volume. The remaining gas was one or more of He or Ar, to obtain a TiO2-supported Pt and Ni catalyst.
2. The application according to claim 1, characterized in that: The loading of Pt relative to the support is 0.1-0.7 wt% of the support, and the loading of Ni relative to the support is 4-8 wt%. In step 1), the molar ratio of acid to titanium source is 1.2-1.5; the crystallization temperature is 190-200℃; and the crystallization time is 24-36 hours.
3. The application according to claim 1, characterized in that: The loading of Pt relative to the support is 0.4-0.6 wt%, and the loading of Ni relative to the support is 4-6 wt%. In step 1), the synthesis of nanosheets consists of a titanium source and an acid, wherein the molar ratio of the acid to the titanium source is 1.2-1.
5.
4. The application according to claim 1, characterized in that: The mixed gas is a mixture containing CO and NO.
5. The application according to claim 1, characterized in that: Pt is uniformly dispersed in the form of single atoms on the second metal component Ni, with Ni particles ranging in size from 4 to 10 nm, and the Ni particles are supported on a TiO2 carrier.
6. The application according to claim 1, characterized in that: Pt forms a single-atom alloy with Ni; the TiO2 support is anatase TiO2 nanosheets.
7. The application according to claim 1, characterized in that: The titanium source used is tetrabutyl titanate or tetraisopropyl titanate; the acid is hydrofluoric acid with a mass concentration of 30%-40%.
8. The application according to claim 1, characterized in that: The Pt source is chloroplatinic acid; the Ni source is nickel nitrate and / or nickel acetate.
9. The application according to any one of claims 1-8, characterized in that: The specific reaction process is as follows: In a fixed bed, a catalyst with a particle size of 40-60 mesh is added, and after reduction with 5-15% volume fraction hydrogen at 400℃-500℃ for 1-2 hours, a reaction gas is introduced in the temperature range of 50-400℃, with a volume hourly space velocity of 10000-50000 ml / (g×h) to obtain the product.
10. The application according to claim 9, characterized in that: Add a catalyst with a particle size of 40-50 mesh, reduce at 400℃-450℃ for 1.5-2h, and pass a reaction gas through the reaction gas in the temperature range of 50-400℃ with a volume hourly space velocity of 20000-30000ml / (g×h) to obtain the product.
11. The application according to claim 9, characterized in that: The reaction gas is a mixture of CO and NO with a volume concentration of 0.1-0.5% by volume, the molar ratio of CO to NO is 1:1.2, and the remaining components of the mixture are one or more of He and Ar.
12. The application according to claim 11, characterized in that: The volume concentrations of CO and NO are 0.1-0.4%.
13. The application according to claim 12, characterized in that: The volume concentrations of CO and NO are 0.1-0.2%.
Citation Information
Patent Citations
Alloyed metal catalysts for the reduction of NOx in the exhaust gases from internal combustion engines containing excess oxygen
US5977012A